VISITOR MANAGEMENT IN THE SITUGEDE ECO-TOURISM AREA - V SriHadi, Cecilia; Roberto, Roberto (Kesatuan Press, 2021)
SituGede is a valuable environmental asset for soil and water ecosystems in the city of Bogor and its surroundings. The productive use of this area can be done through ecotourism. The concept of back to nature, is a contemporary lifestyle that is increasingly popular, especially after the covid 19 pandemic. In order for the function of ecotourism to be carried out in a sustainable manner, collaboration between concepts and stakeholders is a priority. Visitor management is one way that can be taken in an effort to make SituGede a sustainable ecotourism destination